Health literacy of community leaders in the prevention and control of COVID-19: A cross-sectional study: 10.55131/jphd/2024/220301 - Phimha, Surachai; Prasit, Nakarin; Senahad, Nopparat; Aunthakot, Krissana; Pinsuwan, Chanaporn; Sornlorm, Kittipong; Nidthumsakul, Nuttaporn; Heebkaew Padhasuwan, Natnapa (Journal of Public Health and Development, 2024)
Community leaders in Thailand play an important role in preventing and controlling infectious diseases, especially during the COVID-19 pandemic. Hence, risk perception and adequate health literacy among these leaders influence the population. This cross-sectional study aimed to investigate the relationships among health literacy, risk perception factors, and the implementation of COVID-19 prevention and control. A self-administered structured questionnaire was administered to 1,338 community leaders in northeast Thailand to assess the level of implementation of COVID-19 prevention and control measures. Multiple logistic regression was performed to identify the influence of risk perceptions and health literacy on the prevention and control of COVID-19. Approximately 64% of the sample was male, and the participants had an average age of 50.51 ± 8.47 years. The factors associated with moderate and high levels of COVID-19 prevention and control among community leaders were moderate and high levels of perceived susceptibility (adjusted odds ratio [ORadj] = 3.01; 95% CI: 2.13–4.25; p-value < 0.001) and perceived severity (ORadj = 1.73; 95% CI: 1.22–2.45; p-value = 0.023) as well as adequate access (ORadj = 1.56; 95% CI: 1.08–2.25; p-value < 0.001) and adequate understanding (ORadj = 2.29; 95% CI: 1.34–3.93; p-value < 0.001), with a level of statistical significance of 0.05. The incorporation of health literacy and risk perception, especially in dimensions such as access, understanding, perceived susceptibility, and perceived severity, is essential for leaders to possess strong skills in community health development, particularly during crises such as the COVID-19 pandemic.